Theorising multiply disadvantaged young people’s challenges in accessing higher education - Melanie Walker; Faith Mkwananzi (Perspectives in Education, 2015)
This paper sketches an innovative conceptualisation of disadvantaged youth, shaped dialogically by the interactions of theorising and data from a case study at Orange Farm informal settlement in South Africa in 2013. The study focused on the challenges for the young people in this area in accessing higher education. Drawing on Sen’s and Nussbaum’s capability approach, complemented by a theorisation of vulnerability by Misztal and of oppression by Young, the study illustrates how the concepts should be interconnected to generate a framework for understanding the experiences of multiply disadvantaged youth, as well as issues of equity for them in accessing HE. The paper highlights the need to understand young people’s experiences and aspirations using multidisciplinary theorising, in conversation with empirical lives. Overall, advantage is understood as having the freedoms (or capabilities) to live a life each person has reason to value, with genuine opportunities for secure functionings now and in the future. A disadvantaged life, by contrast, would have less or neither.